Propuesta de la documentación del sistema de gestión de seguridad y salud en el trabajo para la empresa Calzado Esmaylis con base a los lineamientos del decreto 1072 de 2015 en la ciudad de Bogotá DC (2022)
With the current legislation that the country has in accordance with Decree 1072 of 2015 companies are under the obligation to adopt a security system and health at work, since the staff will be considered as the most valuable resource when inside the companies, for this reason it is necessary to design the SST that will allow to take care of the safety and health of all personnel involved in their daily activities, since are constantly exposed to accidents that can affect the integrity of both mental and physical of the workers. For this reason, each company that is legally registered must have an SG-SST that has welfare as a priority of its workers, in accordance with the provisions of the Ministry of Labor.The topic of work that will be covered throughout this project is based on a Occupational Health and Safety Management System for the company Calzado Esmaylis because it does not have this system and through which it is intended prevent any type of accident at work and occupational disease, the interest that is presents both professionally and academically is to improve the labor quality of the collaborators to carry out their daily activities with more motivation having Keep in mind that the company is pending their care with all the measures pertinent that are established in Decree 1072 of 2015. The present work intends to carry out an investigation based on the decree 1072 of 2015, covering different branches of engineering. industrial (safety) industry, plant design, statistics, among many others) this to finally 2 design the documentation of the SG-SST complying in this way with what is said in the Decree 1072 of 2015 and in which the methodology of the PDVA cycle "Planning, Do, Verify, Act'', which will allow knowing the current state of the company evaluating the minimum standards required according to the size of the company that is presented in the current legislation. Carrying out the design of the documentation of the SG-SST can be oriented to the company to increase the quality of performance of each of the workers of Esmaylis Footwear, as well as ensuring the comprehensive well-being of each one of them. Initially, an initial diagnosis will be made to allow a better vision of what that is happening in the company and that allows to have a better evaluation in the management of risks and dangers, so that in this way the jobs are evaluated, followed by this, the cost-benefit analysis will be elaborated with respect to the documentation to design. Finally, the respective design of the SG-SST documentation based on decree 1072 of 2015 which will be delivered to the enterprise